Glicerina bruta oriundo da produção do biodiesel no aproveitamento de silagem de sorgo por caprinos mestiços boer em terminação - Bezerra, Higor Fábio Carvalho (2016)
This study aimed to evaluate the effect of crude glycerin from biodiesel production on intake, digestibility, ruminal parameters, quantitative and qualitative characteristics of carcass and beef, protein, energetic and enzymatic profiles of hepatic metabolism, urinary profile and histopathological evaluation of hepatic and renal tissues in crossbred Boer goats finishing. Thirty-two crossbred Boer goats kids (Boer x undefined breed), castrated, with average initial weight of 17.8 ± 2.2 kg, between three and four months old, were assigned in a completely randomized experimental design with four treatments (diets with inclusion levels of crude glycerin of 0, 5, 10 and 15% on fresh matter basis) and eight repetitions. The inclusion of crude glycerin linearly decreased (P<0.05) the intakes of DM and all nutrients, ether extract digestibility, final weight, daily weight gain and total weight gain of animals. Neutral detergent fiber had a quadratic effect (P<0.05), with maximum values estimated in 60.54% at the level of 4.78% of crude glycerin. Addition of crude glycerin levels linearly increased (P<0.05) the ruminal pH, ranging from 6.27 to 6.49. Concentration of NH3-N and microbial protein in the rumen had a linear decrease (P<0.05) by dietary crude protein levels. The lower concentration of microbial protein (322.18 mg/dL) was found with inclusion of 15% and higher concentration (369.31 mg/dL) in treatment without inclusion of crude glycerin. Empty body weight, hot and cold carcass weight linearly decreased (P<0.05) by dietary crude glycerin levels. However, inclusion of crude glycerin did not affect the losses, yield and morphometric characteristics of carcass and physical characteristics of goat meat. There was a linearly decreased on loin eye area and measurement B with inclusion of crude glycerin in diets. Inclusion of crude glycerin associated with approximately 6.6% of methanol leads to a decrease on characteristics related with studied variables of crossbred Boer goats kids as it is increased in diets. However, did not affect carcass measurements and meat quality. Thus, it is suitable to use crude glycerin in goats’ diet with lower methanol content. Crude glycerin did not affect (P>0.05) metabolic profile and renal tissues. Hepatic tissue had deleterious effects with addition of crude glycerin. Inclusion of crude glycerin associated with approximately 6.6% of methanol leads to a decrease on intake, gain, characteristics related to slaughter weight and deleterious xviii effect on hepatic tissue of crossbred Boer goats kids as it is increased in diets. However, did not affect nutrient digestibility, food conversion and feed efficiency, carcass measurements and meat quality and did not cause deleterious effects on renal tissue and serum profiles. Thus, it is suitable to use crude glycerin in goats’ diet with lower methanol content.